Operational radiation safety program for astronauts in low-earth orbit a basic framework : recommendations of the National Council on Radiation Protection and Measurements. (National Council on Radiation Protection and Measurements, 2002)
Meinhold, C.B., Investigator, Non-NASA Center: Natl Council Radiat Prot Meas, Bethesda, MD.
"Issued November 30, 2002."
Keywords: Extraterrestrial radiation -- Safety measures.; Astronauts -- Health and hygiene.; Space medicine.; elektronické knihy; electronic books